5G remote interference management function research and network intelligent optimization - Tinglan WANG; Feng GAO; Peijin LYU; Tairan WU; Wenli LI (Dianxin kexue)
To mitigate the impact of tropospheric radio-duct interference on 5G network, 3GPP has defined functionalities for remote interference management.Based on this functionality, an automated scheme for SetID and gNBID was developed, enabling the reuse of SetID in different tropospheric radio-duct interference regions, striking a balance between efficiency and uniqueness.By analyzing remote interference measurement data from base stations, an intelligent localization and identification method for tropospheric radio-duct interference was summarized.An intelligent network optimization process for identifying the aggressor base stations was created and successfully validated in the network.An effective operational plan was provided for management of 5G tropospheric radio-duct interference, alleviating the constraints on the development of the 5G industry caused by the interference.